2014
DOI: 10.3892/ijmm.2014.1729
|View full text |Cite
|
Sign up to set email alerts
|

Autografting of bone marrow mesenchymal stem cells alleviates streptozotocin-induced diabetes in miniature pigs: Real-time tracing with MRI in vivo

Abstract: Cellular replacement therapy for diabetes mellitus (DM) has received much attention. In this study, we investigated the effect of transplantation of autologous bone marrow-derived mesenchymal stem cells (ABMSCs) in streptozotocin (STZ)-induced diabetic miniature pigs. Miniature pig BMSCs were cultured, labeled with superparamagnetic iron oxide (SPIO) and transplanted into the pancreas of diabetic miniature pigs through targeted intervention. Blood glucose levels, intravenous and oral glucose tolerance test (OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Tang et al [53] investigated the effect of transplantation of autologous BMSCs in streptozotocin-induced DM pigs. The results obtained in the animal model have been showed that transplantation of autologous BMSCs may help to reverse a streptozotocin-induced DM.…”
Section: Bone Marrow Derived Mesenchymal Stem Cells Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [53] investigated the effect of transplantation of autologous BMSCs in streptozotocin-induced DM pigs. The results obtained in the animal model have been showed that transplantation of autologous BMSCs may help to reverse a streptozotocin-induced DM.…”
Section: Bone Marrow Derived Mesenchymal Stem Cells Transplantationmentioning
confidence: 99%
“…Obviously these data suggested that autologous BMSCs implantation might be useful as alternative strategy of DM. Overall, majority investigators have been concluded that the transplantation of BMSCs aimed alternative treatment of DM added to conventional strategy is safe and effective [52,53] .…”
Section: Bone Marrow Derived Mesenchymal Stem Cells Transplantationmentioning
confidence: 99%
“…Insulin injection, the predominant treatment for T1D, is effective to ameliorate the hyperglycaemia but incompetent to relieve the autoimmunity and to regenerate lost islets. The recent progress in regenerative medicine, especially stem cell therapy, has suggested several novel and potential cures for T1D . Mesenchymal stem cell‐based cell therapy is one of them .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, numerous previous studies support the idea that bone marrow mesenchymal stem cells (BMSCs) could be an effective and novel therapy modality for various diseases; e.g., sepsis, endotoxemia, diabetes, lung injury, etc. [3][4][5][6][7][8][9][10][11]. Therefore, our objective was to investigate whether the use of bone marrow mesenchymal stem cells as a new cellular therapy modality could ameliorate kynurenine (KYN) production by endothelial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%